Analisis Beberapa Faktor Yang Mempengaruhi Kinerja Karyawan Pada Perpustakaan Pusat Universitas Muhammadiyah Surakarta - Kuwerasari, Novita; , Drs. Kusdiyanto, S.E., M.Si (2016)
The purpose of this study was to determine some of the factors that affect the performance of employees in Central Library of the Muhammadiyah Surakarta University in terms of the factors that influence that the work environment, work discipline, and job satisfaction. This study is a survey research with a quantitative approach. Tests were performed in this study using a test instrument that research validity and reliability test, test the classical assumption of normalistas test, test the hypothesis that multiple linear regression, t test, F test and coefficient of determination or R2. The data in this study are primary data obtained by distributing a questionnaires to respondents, where respondents here are employees in Central Library of the Muhammadiyah Surakarta University. Samples taken in the study were 36 employees. Based on the results of the study showed that the work discipline variable is a variable that has a dominant influence on the performance of employees in Central Library of the Muhammadiyah Surakarta University. In addition the results showed that there is a simultaneous and significant influence between the variables of the work environment, work discipline and job satisfaction on employee performance, results obtained coefficient of determination or R2 of 74,1% of the variation changes the performance of the employee fluctuation due to changes in the work environment variables, work discipline, and job satisfaction. While the remaining 25,9% were caused by other factors not analyzed in the model used in the study. Keywords: Work Environment, Work Discipline, Job Satisfaction, Performance Employees.